Cody

Solution 2479184

Submitted on 5 Jun 2020 by Ramesh Kumar V
This solution is locked. To view this solution, you need to provide a solution of the same size or smaller.

Test Suite

Test Status Code Input and Output
1   Pass
x = [1 2 5 2 2 7 8 3 3 1 3 8 8 8]; y_correct = [2 3]; assert(isequal(threeTimes(x),y_correct))

x = 1 1 2 2 2 3 3 3 5 7 8 8 8 8 y = 1 2 3 5 7 8 m = 14 n = 6 count = 0 count = 1 c = 1 count = 2 c = 2 c = 2 c = 2 c = 2 c = 2 c = 2 c = 2 c = 2 c = 2 c = 2 c = 2 c = 2 c = 2 count = 0 c = 2 0 c = 2 0 count = 1 c = 2 1 count = 2 c = 2 2 count = 3 c = 2 3 c = 2 3 c = 2 3 c = 2 3 c = 2 3 c = 2 3 c = 2 3 c = 2 3 c = 2 3 c = 2 3 count = 0 c = 2 3 0 c = 2 3 0 c = 2 3 0 c = 2 3 0 c = 2 3 0 count = 1 c = 2 3 1 count = 2 c = 2 3 2 count = 3 c = 2 3 3 c = 2 3 3 c = 2 3 3 c = 2 3 3 c = 2 3 3 c = 2 3 3 c = 2 3 3 count = 0 c = 2 3 3 0 c = 2 3 3 0 c = 2 3 3 0 c = 2 3 3 0 c = 2 3 3 0 c = 2 3 3 0 c = 2 3 3 0 c = 2 3 3 0 count = 1 c = 2 3 3 1 c = 2 3 3 1 c = 2 3 3 1 c = 2 3 3 1 c = 2 3 3 1 c = 2 3 3 1 count = 0 c = 2 3 3 1 0 c = 2 3 3 1 0 c = 2 3 3 1 0 c = 2 3 3 1 0 c = 2 3 3 1 0 c = 2 3 3 1 0 c = 2 3 3 1 0 c = 2 3 3 1 0 c = 2 3 3 1 0 count = 1 c = 2 3 3 1 1 c = 2 3 3 1 1 c = 2 3 3 1 1 c = 2 3 3 1 1 c = 2 3 3 1 1 count = 0 c = 2 3 3 1 1 0 c = 2 3 3 1 1 0 c = 2 3 3 1 1 0 c = 2 3 3 1 1 0 c = 2 3 3 1 1 0 c = 2 3 3 1 1 0 c = 2 3 3 1 1 0 c = 2 3 3 1 1 0 c = 2 3 3 1 1 0 c = 2 3 3 1 1 0 count = 1 c = 2 3 3 1 1 1 count = 2 c = 2 3 3 1 1 2 count = 3 c = 2 3 3 1 1 3 count = 4 c = 2 3 3 1 1 4 k = 0 k = 1 z = 2 k = 2 z = 2 3

2   Pass
x = [1 1 1]; y_correct = [1]; assert(isequal(threeTimes(x),y_correct))

x = 1 1 1 y = 1 m = 3 n = 1 count = 0 count = 1 c = 1 count = 2 c = 2 count = 3 c = 3 k = 0 k = 1 z = 1

3   Pass
x = [5 10 -3 10 -3 11 -3 5 5 7]; y_correct = [-3 5]; assert(isequal(threeTimes(x),y_correct))

x = -3 -3 -3 5 5 5 7 10 10 11 y = -3 5 7 10 11 m = 10 n = 5 count = 0 count = 1 c = 1 count = 2 c = 2 count = 3 c = 3 c = 3 c = 3 c = 3 c = 3 c = 3 c = 3 c = 3 count = 0 c = 3 0 c = 3 0 c = 3 0 count = 1 c = 3 1 count = 2 c = 3 2 count = 3 c = 3 3 c = 3 3 c = 3 3 c = 3 3 c = 3 3 count = 0 c = 3 3 0 c = 3 3 0 c = 3 3 0 c = 3 3 0 c = 3 3 0 c = 3 3 0 count = 1 c = 3 3 1 c = 3 3 1 c = 3 3 1 c = 3 3 1 count = 0 c = 3 3 1 0 c = 3 3 1 0 c = 3 3 1 0 c = 3 3 1 0 c = 3 3 1 0 c = 3 3 1 0 c = 3 3 1 0 count = 1 c = 3 3 1 1 count = 2 c = 3 3 1 2 c = 3 3 1 2 count = 0 c = 3 3 1 2 0 c = 3 3 1 2 0 c = 3 3 1 2 0 c = 3 3 1 2 0 c = 3 3 1 2 0 c = 3 3 1 2 0 c = 3 3 1 2 0 c = 3 3 1 2 0 c = 3 3 1 2 0 count = 1 c = 3 3 1 2 1 k = 0 k = 1 z = -3 k = 2 z = -3 5